2016
DOI: 10.1111/asj.12613
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationships between meat quality traits and fatty acid composition in Japanese black cattle

Abstract: Genetic parameters were estimated to investigate the relationships between meat quality traits and fatty acid composition from 11 855 Japanese Black cattle. The meat quality traits included beef marbling score (BMS), beef color score, firmness of beef (FIR), texture of beef (TEX) and beef fat color score (BFS). The data on fatty acid composition included oleic acid and monounsaturated fatty acids (MUFA) contents, the ratio of MUFA to saturated fatty acids (MUS) and the ratio of elongation. The heritability est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 47 publications
6
20
1
3
Order By: Relevance
“…Relationships between the increase in fat amount and saturated (SFA), monounsaturated (MUFA) and decrease in polyunsaturated (PUFA) proportions were reported by De Smet et al [29], Yang et al [30], and Wood et al [31]. In several studies [32,33], the heritability estimates of fatty acid composition in cattle indicated that fatty acids are determined genetically. Moreover, it is known that IMF enriched in SFA and MUFA are resulting mainly from de novo synthesis and PUFA is resulting mainly from the diet [32].…”
Section: Fatty Acid Profi Lesmentioning
confidence: 92%
“…Relationships between the increase in fat amount and saturated (SFA), monounsaturated (MUFA) and decrease in polyunsaturated (PUFA) proportions were reported by De Smet et al [29], Yang et al [30], and Wood et al [31]. In several studies [32,33], the heritability estimates of fatty acid composition in cattle indicated that fatty acids are determined genetically. Moreover, it is known that IMF enriched in SFA and MUFA are resulting mainly from de novo synthesis and PUFA is resulting mainly from the diet [32].…”
Section: Fatty Acid Profi Lesmentioning
confidence: 92%
“…These records have been used and published by Inoue et al. (2016) and Inoue, Shoji, Honda, and Oyama (2017) to evaluate the genetic relationship between meat quality traits; however, the objective of the present study differed from that of the aforementioned studies. Descriptive statistics for carcass and fatty acid traits are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Konsumsi daging yang mengandung asam lemak jenuh tinggi dapat menyebabkan peningkatan kolesterol plasma yang berimplikasi pada penyakit beberapa penyakit diantaranya kardiovaskuler (Alvarenga et al, 2015). Tingginya nilai heritabilitas komposisi asam lemak berkisar 0,60-0,63 (Inounu et al, 2017) menandakan bahwa seleksi gen pengontrol karakteristik karkas dan sifat perlemakan akan efektif meningkatkan mutu genetik daging daging domba. Salah satu upaya yang dapat dilakukan untuk menghasilkan daging domba dengan mutu genetik yang tinggi, yaitu seleksi berbasis molekuler melalui identifikasi gen pengontrol asam lemak pada domba.…”
Section: Pendahuluanunclassified